PENGUJIAN KONFIGURASI PIEZOELEKTRIK PENGHASIL TEGANGAN LISTRIK DARI ENERGI MEKANIK - Riska Ekawita; Rahmat Awaludin Salam; Nolla Kusumawardani; elfi yuliza (Prodi Fisika FST UNJA, 2021)
There are enormous of natural resources as alternative electrical energy to be developed in Bengkulu province. It’s located in west coast of Sumatera Island and faces on Indian Ocean make Bengkulu province abundant wind energy. Piezoelectric is a material that produces electrical while the pressure applied on the surface. In this research, a preliminary study of characteristic of piezoelectric was carried out to produce electrical from mechanical energy generated from wind. The output voltage from some piezoelectric configurations was measured. Furthermore, a prototype of wind energy conversion to electrical energy was enlarged to search piezoelectric characteristic too. The measurement results show that the series piezoelectric configuration produces a higher electric voltage than the parallel arrangement. The greater the mechanical energy received on the piezoelectric surface, the higher the electric voltage generated by the piezoelectric. Four piezoelectric in series configuration produce 3.5 volts of voltage while 3.6 joules mechanical energy applied on their’s surfaces. By using the prototype of wind energy conversion, it is found that the wind velocity influence the obtained of voltage. There is a linear relationship between wind speed and the voltage generated.